Manifestations of school abuse in students from urban and rural areas schools - Aliaga Sandoval, Cecilia Gladys (2017)
The study had as general objective to describe and compare the manifestations of school abuse in students from urban and rural areas schools. It was conducted as a basic research at a comparative level; a questionnaire, initially validated by experts, was used as an information retrieval tool, and after it was corrected, it was validated by a pilot test with students. This instrument was applied to 197 students from María Inmaculada School (Huancayo), 783 students from Túpac Amaru School (Chilca) and 58 students from Istay School (Huancavelica) during the years 2012, 2013 and 2014, respectively. Bronfenbrenner’s ecological theory and Arnold Buss’s behavioral theory were used to support the research findings. From those findings, it can be affirmed that in the process of peer-to-peer interaction between students from urban and rural public schools, there are abuse manifestations such as physical aggressions: hair pulling, pushing, kicking, blows in various parts of the body, and verbal expressions: nicknames, insults, humiliations. In addition, it was found out the practice of cyberbullying, happy slapping and dating violence; typical manifestations of school violence in urban areas, but also present in rural areas. This last finding is related to the access to the mass media, such as fixed/mobile telephony and the internet, which have coverage in these areas. It has been concluded that the study developed during the years 2012, 2013 and 2014 in public schools from urban and rural areas reveals the prevalence of physical aggressions and verbal aggressions between peers.   DOI: https://doi.org/10.31876/sl.v1i1.2